2011
DOI: 10.1088/0004-637x/735/2/75
|View full text |Cite
|
Sign up to set email alerts
|

H Ii Region Luminosity Function of the Interacting Galaxy M51

Abstract: We present a study of H II regions in M51 using the Hubble Space Telescope ACS images taken as part of the Hubble Heritage Program. We have catalogued about 19,600 H II regions in M51 with Hα luminosity in the range of L = 10 35.5 erg s −1 to 10 39.0 erg s −1 . The Hα luminosity function of H II regions (H II LF) in M51 is well represented by a double power law with its index α = −2.25±0.02 for the bright part and α = −1.42±0.01 for the faint part, separated at a break point L = 10 37.1 erg s −1 . This break w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
55
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(60 citation statements)
references
References 56 publications
(157 reference statements)
5
55
0
Order By: Relevance
“…In addition, we use the catalog of 1507 GMCs identified in the PAWS area (Colombo et al 2014a), the catalog of 7215 grouped H II regions (i.e., giant H II regions identified via a friends-of-friends algorithm; Lee et al 2011), and the catalog of 3812 stellar clusters identified in and characterized by HST a + UVBI H imaging (Chandar et al 2016). …”
Section: Datamentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, we use the catalog of 1507 GMCs identified in the PAWS area (Colombo et al 2014a), the catalog of 7215 grouped H II regions (i.e., giant H II regions identified via a friends-of-friends algorithm; Lee et al 2011), and the catalog of 3812 stellar clusters identified in and characterized by HST a + UVBI H imaging (Chandar et al 2016). …”
Section: Datamentioning
confidence: 99%
“…A quantitative analysis of star formation in the different zones of the selected spiral arm region is made utilizing catalogs of (giant) H II regions (Lee et al 2011) and young (10 Myr) stellar clusters (Chandar et al 2016) identified in HST images (see Section 3.2.2).…”
Section: Star Formation Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…6), regions of strong star formation in the spiral arms show flat spectral indices. Regions of high star formation are bulging into the interarm region, specifically in the inner southeastern region where several H ii regions exist in the interarm regions (Lee et al 2011). Figure 7 shows the radial spectral index profile, created from the mean flux densities at 1.4 GHz and 151 MHz in concentric rings in the galaxy's plane and then computing the spectral index.…”
Section: Spectral Index Map Of M 51mentioning
confidence: 99%
“…It is therefore impossible to make a physical connection between a SN and the H  region in which its progenitor formed. However such star-forming regions are gathered in groups (see for instance M 51 in Lee et al 2011), concentrated in spiral arms whose lifetimes are longer than the time scale for a prompt SN. (See Kauffmann et al 2003, for details on the star formation history of galaxies.)…”
Section: Introductionmentioning
confidence: 99%